A computerized database (CorMol) on the molluscan fauna from the Mediterranean reef ecosystems: Part I, the coralligenous formations. (10th December 2015) - Poursanidis, Dimitris; Koutsoubas, Drosos
Abstract: In the Mediterranean Sea, infralittoral and circalittoral rocky bottoms (from 15 to 120 m) are characterized by a biogenic habitat, named "coralligenous", formed by the concretion of calcareous organisms, mainly algal thalli, and to a lesser extent by animal skeletons. This complex habitat is inhabited by a rich fauna that belongs to different taxonomic groups. Sponges, bryozoans, cnidarians and ascidians are the most common sessile organisms that inhabit the area, while crustacea and molluscs are the most common mobile organisms. Little information on the diversity of the molluscs that thrive in the coralligenous habitat is known, though this information is highly important for biodiversity management purposes. A database for the molluscs of the coralligenous habitat was compiled and a method implemented for the management of this information. More than 511 species of molluscs have been recorded so far from the coralligenous formations, the majority of which belong to the class Gastropoda (357 sp.) followed by Bivalvia (137 sp.), Polyplacophora (14 sp.), Cephalopoda (2 sp.) and Scaphopoda (1 sp.). Among these, the gastropod Luria lurida (Linnaeus, 1758) and Charonia lampas (Linnaeus, 1758), the endemic bivalve Pinna nobilis (Linnaeus, 1758) and the endolithic bivalve Lithophaga lithophaga (Linnaeus, 1758), are protected by international conventions.